Enhanced bioadhesivity of dopamine-functionalized polysaccharidic membranes for general surgery applications. (15th October 2016) - Scognamiglio, F.; Travan, A.; Borgogna, M.; Donati, I.; Marsich, E.; Bosmans, J.W.A.M.; Perge, L.; Foulc, M.P.; Bouvy, N.D.; Paoletti, S.
Graphical abstract: Abstract: An emerging strategy to improve adhesiveness of biomaterials in wet conditions takes inspiration from the adhesive features of marine mussel, which reside in the chemical reactivity of catechols. In this work, a catechol-bearing molecule (dopamine) was chemically grafted onto alginate to develop a polysaccharide-based membrane with improved adhesive properties. The dopamine-modified alginates were characterized by NMR, UV spectroscopy and in vitro biocompatibility. Mechanical tests and in vitro adhesion studies pointed out the effects of the grafted dopamine within the membranes. The release of HA from these resorbable membranes was shown to stimulate fibroblasts activities ( in vitro ). Finally, a preliminary in vivo test was performed to evaluate the adhesiveness of the membrane on porcine intestine (serosa). Overall, this functionalized membrane was shown to be biocompatible and to possess considerable adhesive properties owing to the presence of dopamine residues grafted on the alginate backbone. Statement of Significance: This article describes the development of a mussels-inspired strategy for the development of an adhesive polysaccharide-based membrane for wound healing applications. Bioadhesion was achieved by grafting dopamine moieties on the structural component on the membrane (alginate): this novel biomaterial showed improved adhesiveness to the intestinal tissue, which was demonstrated by both in vitro and in vivo studies. Overall, this study points out how this nature-inspired strategy may be successfully exploited for the development of novel engineered biomaterials with enhanced bioadhesion, thus opening for novel applications in the field of general surgery.